Pengetahuan Kecacingan Menggunakan Media Video Pada Siswa Sekolah Dasar - Sahariyani, Menik; Sari, Rita Kartika; Tasyahuri, Syabila Aldiffah (Jurnal Kedokteran Universitas Palangka Raya, 2024)
Helminthiasis in children still occurs in Seren Rembang. Educational video can enhance knowledge and attitudes in order to reduce the morbidity of Helminthiasis.  This study aims to determine the impact of providing Helminthiasis educational video on the level of knowledge and attitude of students at SDN Seren Rembang. Research method is Quasi Experimental using a "pre-post test one group only" design. Total sampling involved 37 students of SDN Seren Rembang. Two questionnaires utilized to measure the knowledge and the attitude. Data analysis using the Paired Sample t-test. Result : Educational video is able to increase the average level of students' knowledge and attitude from 4.43 into 7.75, and from 30.43 into 33.37, respectively. Paired samples t-test is significant for both knowledge (p = 0,000), and attitude (p = 0,002). This study conclude that providing Helminthiasis educational video affect the level of knowledge and attitude of students at SDN Seren Rembang.